Screening of Subclinical Hypothyroidism in Antenatal Women and its Impact on Pregnancy Outcomes - Razzaq, Kashif; Anwar, Rabiah; Noor, Nusrat; Tariq, Amera; Imran, Ayesha; Iftikhar, Bushra; Anwar, Sobia (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To screen subclinical hypothyroid cases in antenatal checkups and to assess the impact of this condition on the fetomaternal outcome.Study Design: Prospective cohort study.Place and Duration of Study: Department of Gynecology and Obstetrics, Pakistan Naval Ship Shifa Hospital Karachi Pakistan, from Jun 2019 to May 2020.Methodology: During the study period, all singleton pregnant women with no comorbid, having booking visits during the first trimester of pregnancy were included. Three thousand four hundred fifty obstetric patients fulfilled the inclusion criteria. Their serum TSH and free T4 and T3 were sent along with routine antenatal investigations. Pregnancy specific first-trimester normal reference values of TSH (0.03-2.3µU/ml) and free T4 (0.8-1.8ng/dl) were used to classify pregnant women into euthyroid (controls) and overt and subclinical hypothyroid (cases). Comparison of antenatal complications (gestational diabetes, gesta tional hypertension, pre-eclampsia, and preterm labour), mode of delivery (vaginal delivery, cesarean section) and perinatal outcome (intrauterine growth restriction, intrauterine fetal death, low APGAR score at 5 min) was made among both the groups.Results: Hypothyroid women had significantly increased risk of gestational hypertension (RR= 4.795% CI=2.902 to 7.773, p